1962
DOI: 10.1115/1.3684306
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Radial Temperature Gradient on the Instability of Fluid Flow in an Annulus With an Inner Rotating Cylinder

Abstract: The problem of instability of diabatic flow between rotating, concentric cylinders has been studied analytically.The basic equations were reduced to a form identical to that of a similar instability fluid flow problem, namely, the instability of a horizontal layer of fluid heated from below. The latter problem has been solved by Pellew and Southwell, and their solution was used to calculate and predict the instability of diabatic flow in the annulus. The results of the analysis show that heating of the inner r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 8 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…A similar effect was also pointed out in the works [22,27,29]. However, a physical interpretation of this phenomenon can be hardly proposed.…”
Section: Numerical Methods Of the Solution And Its Verificationsupporting
confidence: 57%
See 1 more Smart Citation
“…A similar effect was also pointed out in the works [22,27,29]. However, a physical interpretation of this phenomenon can be hardly proposed.…”
Section: Numerical Methods Of the Solution And Its Verificationsupporting
confidence: 57%
“…They revealed Taylor vortices together with other effects depending on the buoyancy associated with the axially oriented gravity. Peculiarities of instability phenomena in a small gap were considered in the works [27][28][29]. Experimental investigations for gases were performed by [30,31] and for liquids by [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental investigation by Becker and Kaye [10] showed that addition of axial flow delays the transition process that leads to formation of Taylor vortices. The study of Martin and Hasoon [11] indicates the same gap radius ratio η effect on critical Taylor number as in the cases without axial flow.…”
Section: Taylor-couette Flow Phenomenamentioning
confidence: 99%
“…There are several studies which looked into the heat transfer phenomena associated with the Taylor-Couette flow [10,[15][16][17]. Most of these investigations focused on measurements of the inner cylinder heat transfer coefficients for cases with radial temperature gradient within the annulus gap.…”
Section: Plr Pump Applicationmentioning
confidence: 99%
“…The heat transfer coefficient (HTC) for the rotor-stator air-gap is determined by using the correlation developed by Becker and Kaye [5], [6] :…”
Section: System Level Thermal Modelingmentioning
confidence: 99%